A vibration-driven locomotion robot excited by time-varying stiffness. (1st April 2023) - Wang, Xiaojian; Meng, Lili; Yao, Yuhui; Li, Hongguang
Highlights: A vibration-driven robot structure with time-varying stiffness is proposed for the first time. The asymmetry of the system is caused by time-varying stiffness. Forward and reverse walking is realized by controlling the frequency of the input waveform. A vibration-driven robot prototype based on the conical dielectric elastomer actuator is established. Abstract: This investigation is aimed to propose a vibration-driven friction-induced robot structure with time-varying stiffness. Different from the common vibration-driven robots with force excitation, a vibration-driven robot with sinusoidal stiffness excitation is proposed for the first time. The obtained results reveal the nonlinear driving mechanism of the vibration-driven system under the coupling action of time-varying stiffness and large deformation. First, the dynamic model of a vibration-driven robot excited by the periodic stiffness variation is introduced, and the equations of motion of the robot are discussed. On this basis, the dynamic response of the robot is evaluated via the incremental harmonic balance method, and the effects of the load mass and stiffness are methodically examined and discussed. Finally, an experimental test system based on the dielectric elastomer actuator is established to verify the dynamic performance of the vibration-driven robot excited by the periodic stiffness change. It is found that compared with the common vibration-driven robots, the vibration-driven robot with sinusoidal stiffness excitation can move in both directions avoiding anisotropic friction construction or cumbersome input waveform selection, by controlling the frequency of the input waveform. The result expands the application of the intellectual structure in the field of vibration-driven robots. Graphical abstract: Image, graphical abstract